Pregnancy outcomes in women with pulmonary hypertension: a retrospective study in China - Chengtian Lv; Yuwen Huang; Guangyuan Liao; Lichan Wu; Dunjin Chen; Yuanmei Gao (BMC, 2023)
Abstract Background In recent years, with the development of monitoring conditions and the application of pulmonary vascular-targeted drugs, pregnancy outcomes in women with pulmonary hypertension (PH) have improved, but the maternal mortality rate is still high. The purpose of this study was to describe the maternal-foetal outcomes in pregnant women with PH. Methods The clinical data of 154 pregnant women with PH who were admitted to the Third Affiliated Hospital of Guangzhou Medical University from January 2011 to December 2020 were collected and descriptively analysed. Results Among the 154 pregnant women with PH, 6 (3.9%) had idiopathic pulmonary arterial hypertension (iPAH), 41 (26.6%) had pulmonary arterial hypertension (PAH) associated with congenital heart disease (CHD-PAH), 45 (29.2%) had PAH related to other diseases (oPAH), and 62 (40.3%) had PH related to left heart disease (LHD-PH). The systolic pulmonary artery pressure (sPAP) was 36-49 mmHg in 53.2% of the patients, 50-69 mmHg in 22.1% of the patients and ≥ 70 mmHg in 24.7% of the patients. Five (3.2%) pregnant women died within 1 week after delivery; iPAH patients had the highest mortality rate (3/6, 50%). Fifty-four patients (35.1%) were admitted to the intensive care unit (ICU), and the incidence of heart failure during pregnancy was 14.9%. A total of 70.1% of the patients underwent caesarean section; 42.9% had premature infants; 28.6% had low-birth-weight (LBW) infants; 13.0% had very-low-birth-weight (VLBW) infants; 3.2% had extremely-low-birth-weight (ELBW) infants; 61% had small for gestational age (SGA) infants; and 1.9% experienced neonatal mortality. Conclusion There were significant differences in the maternal-foetal outcomes in the iPAH, CHD-PAH, oPAH and LHD-PH groups. Maternal mortality was highest in the iPAH group; therefore, iPAH patients should be advised to prevent pregnancy. Standardized and multidiscipline-assisted maternal management is the key to improving maternal-foetal outcomes.